The Medieval translator : = Traduire au Moyen Âge - International conference on the theory and practice of translation in the Middle Ages (Brepols (éditions), 2007)
Fundamental to all translation work, the concept of displacement allows one to take into account the multiple successive states inhering in a single text, and to interpret these variations. Translation is, in effect, a form of transfer; more specifically, it involves a movement from one context to another, be it national, social, political, historical, linguistic or religious. The texts examined here illustrate, each in their unique way, the relationship between contextual change and audience. They are also the product of subtle interactions between a variety of elements, the result of which is a reinvention of their respective roles and uses over time. For example, a text intending to entertain may also have educational outcomes; a book of local miracles may attract pilgrims and contribute to the economic life of a monastery; a text and its translations may at some point be appropriated for polemical purposes, while a library of translated texts founded on humanist principals may also serve political ends. Furthermore, each successive adaptation and its accompanying annotations impacts upon the tonality of a text. While this diversity of meanings may inspire some (such as the medieval poet Marie de France), it moreover raises a number of important and difficult questions for the modern translator. How, for example, does one translate the harmonics underlying a series of mystical puns? The solution usually involves a compromise that both enhances and undermines the translated text.This volume presents a selection of twenty-eight papers delivered at the Seventh International Conference dedicated to The Theory and Practice of Translation in the Middle Ages, which took place at the University of Paris III Nouvelle Sorbonne in July 2004. The period covered by the texts and their translations extends from antiquity to the present day. The literary and critical breadth of these papers, as well as the rigorous interrogation of the modern translation theory, illustrates the remarkable vitality and diversity of current scholarship in this field.
Keywords: Traducteurs Moyen âge Actes de congrès; Traduction Moyen âge Actes de congrès; Littérature Traduction Moyen âge Actes de congrès; Anglais (langue) Traduction Actes de congrès; Littérature religieuse Traductions Actes de congrès; Philosophie médiévale Traductions Actes de congrès; Languages and Literature; English Language and Literature